2020
DOI: 10.29309/tpmj/2020.27.06.4675
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of obstructive coronary artery disease in patients undergoing valvular heart disease surgery.

Abstract: Objectives: To determine the frequency of obstructive coronary artery disease in patients undergoing valvular heart disease surgery. Study Design: Cross-sectional study. Setting: Department of Cardiology, Faisalabad Institute of Cardiology, Faisalabad. Period: Six months, from 02 February, 2017 to 01 August, 2017. Material & Methods: After taking approval from hospital ethical committee, patients coming through outpatient department who fulfilled the inclusion criteria were enrolled and informed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…95% CI; 2.44-6.01], respectively. A study by Ahmad M et al13 in our local population reported obstructive CAD in 29.3% out of the study sample of 140 cases of VHD. Study further reported the incidence of obstructive CAD was 22.4% in patients with VHD of rheumatic etiology, close to over observation of 24.6%.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…95% CI; 2.44-6.01], respectively. A study by Ahmad M et al13 in our local population reported obstructive CAD in 29.3% out of the study sample of 140 cases of VHD. Study further reported the incidence of obstructive CAD was 22.4% in patients with VHD of rheumatic etiology, close to over observation of 24.6%.…”
mentioning
confidence: 60%
“…[8][9][10][11] The reported prevalence of concomitant CAD varies from the smallest of 9% to as high as 41% depending on the size of the sample, type of the VHD, and definition of CAD used by these studies. 5,12,13 One of the largest studies conducted in the United States of America included 5,360 patients of VHD without a known history of CAD, the prevalence of concomitant CAD was reported in around 19.3% in coronary CT/ diagnostic coronary angiography. 14 Considering the growing prevalence and prognostic implications of concomitant CAD in patients undergoing surgical procedures for VHD, a coronary angiographic assessment is recommended by the "American Heart Association / American College of Cardiology (AHA/ACC) guidelines", especially for the patients above 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El cateterismo cardiaco es un procedimiento médico que puede conllevar a riesgos para el paciente, pero su indicación en este grupo de pacientes está establecida como un protocolo y guía en el manejo de muchas patologías cardiacas. 16 La prevalencia de enfermedad coronaria significativa en pacientes con estenosis aortica severa del HNGAI-EsSalud, fue de 16.6% , realizado en dos años con un total de 120 pacientes comparado con el estudio de Ahmad y col(2020) 9 , del Instituto de Cardiología Faisalabad, (Pakistan). en un periodo de seis meses, un estudio de 140 casos, donde la prevalencia hallada de enfermedad coronaria significativa en pacientes con estenosis aortica severa fue 24.2 % .…”
Section: Discussionunclassified